1984
DOI: 10.1016/0014-5793(84)81337-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pH and inhibitors on the absorption spectrum of cobalt(II)‐substituted carbonic anhydrase III from bovine skeletal muscle

Abstract: Bovine apocarbonic anhydrase III has been prepared by incubation with 2-c~boxy-l,lO-phenanthroIine at pH 5.5, The Co(II)-substituted enzyme has been prepared and its absorption spectrum has been studied. The spectrum is nearly pH-independent above pH 6. It is very similar to the high pH spectral forms of Co(II)-carbonic anhydrases I and II. The spectra of complexes with the sulfonamide inhibitor, acetazolamide, and with CN-and NCO-are virtually identical to the spectra of the corresponding complexes with Co(II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In fact, the metal ion ligands as well as a number of amino acid residues forming hydrogen bond networks in the active site are conserved in all three isoenzymes [l]. The absorption spectra of the Co(I1)-substituted derivatives are quite similar suggesting that the metal ion coordination geometries are almost identical in isoenzymes I, 11, and 111 [6]. Since the interconversion between C 0 2 and HCO; is thought to take place in the immediate vicinity of the metal ion, it seems reasonable to assume that the essential features of the catalytic mechanism are common to all three isoenzymes, and that the kinetic differences reflect a fine-tuning of the catalytic activity that depends on isoenzyme-specific differences in the active-site structures [ 1, 171.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the metal ion ligands as well as a number of amino acid residues forming hydrogen bond networks in the active site are conserved in all three isoenzymes [l]. The absorption spectra of the Co(I1)-substituted derivatives are quite similar suggesting that the metal ion coordination geometries are almost identical in isoenzymes I, 11, and 111 [6]. Since the interconversion between C 0 2 and HCO; is thought to take place in the immediate vicinity of the metal ion, it seems reasonable to assume that the essential features of the catalytic mechanism are common to all three isoenzymes, and that the kinetic differences reflect a fine-tuning of the catalytic activity that depends on isoenzyme-specific differences in the active-site structures [ 1, 171.…”
Section: Discussionmentioning
confidence: 99%
“…The most characteristic, specific feature of the active site of isoenzyme I11 is the presence of some basic amino acid residues, such as Lys-64 and Arg-67, in a hydrophilic part of the active site [l, 181. The positive charges from these residues are thought to stabilize the metal-bound hydroxide ion [5,6,191.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co(II)‐substituted NGCA was prepared by adding the chelator 2‐carboxy‐1,10‐phenantroline (synthesized according to Corey et al . [16]) to a solution of the enzyme followed by dialysis against an excess of CoSO 4 as described by Engberg and Lindskog [17]. The excess of CoSO 4 was removed by dialysis against several changes of 50 m m Hepes/NaOH, pH 8.0.…”
Section: Methodsmentioning
confidence: 99%
“…(7)) is the only or at least a dominant reaction that takes place when sulfonamides bind to a CA, meaning that the intrinsic binding reaction is between the negatively charged sulfonamide to such form of CA where the fourth ligand bound to the Zn II in the active site is electrostatically neutral water molecule. The first indication that the fourth reaction occurs was the spectral evidence on Co-containing CA enzyme (Engberg and Lindskog, 1984; Tu and Silverman, 1986). However, a more recent neutron-diffraction crystal structure of acetazolamide bound to CA II from McKenna laboratory (Fisher et al ., 2012 b ) directly showed that the sulfonamide amino group possesses only one proton and thus the group is deprotonated and negatively charged when bound to the CA II.…”
Section: Observed Versus Intrinsic Thermodynamic Binding Parametersmentioning
confidence: 99%